The use of Merit-Kiriya-Wathu 3 Principles for Improving the Quality of Life of the Elderly in the Northeastern Region : The use of Merit-Kiriya-Wathu 3 Principles for Improving the Quality of Life of the Elderly in the Northeastern Region - Nomrawee, Phramaha Amnoy; Boranmoon, Prapit; Phookodhin, Uthai; Chaloeipot, Suwanan (RATANABUTH JOURNAL, 2023)
Research on this subject purpose 1) to study the development of the quality of life of the elderly in the northeast 2) to study the use of merit-kiriyawathu 3 for the development of the quality of life of the elderly in the northeast 3) To suggest the use of Meritkiriyawathu 3 for improving the quality of life of the elderly in the northeastern region. The sample used in the research were 86 elderly people aged 60 years and over, both. The tool used to collect data was a questionnaire. The statistics used to analyze data from the questionnaire were frequency, percentage, mean, standard deviation. The research found that 1) The development of the quality of life of the elderly in the northeastern region, including all 3 aspects, was at a high level. When considering each side, the averages can be ordered from descending to the lowest, namely the 2nd aspect of living conditions, followed by the 2nd aspect of physical condition, and the least of the 1st aspect of emotional condition. 2). A model for enhancing attitudes towards learning Thai dialects for children and adolescents in the Upper Northeast of Sukapi. Overall, the 4 aspects are very high. Considering each aspect, it can be ranked by the mean of the least to least. The third is the key (Q), the second is the Chi (thinking) and the least is the first (listening). 3) The use of the principle of merit-kiriyawathu 3 for improving the quality of life of the elderly in the northeastern region, including all 3 aspects, was at a high level. When considering each side, it can be ranked in order of average from descending, namely the 2nd aspect of precepts, the 3rd aspect of prayer, and the least aspect of the 1st aspect of alms giving. 4) Handbook for the promotion of attitudes towards learning Thai dialects for children and youth in accordance with the Suchitipoli principle, the lower northeast region It was found that according to the principles and reasons, the objectives of the promotion of Thai language learning for children and youth according to the Supuli principle, the activities used Operating procedures Expected results Monitoring and evaluation.